Behçet's Syndrome Treatment: A Meta-Analysis Comparing Efficacy and Safety of Immunosuppressants and Biologics - Herdian Prima Arionata; Najirman; Eka Kurniawan (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2025)
Background: Behçet's syndrome (BS) is a chronic inflammatory disorder characterized by recurrent oral and genital ulcers, uveitis, and skin lesions. Immunosuppressants and biologics are commonly used to manage BS, but their comparative efficacy and safety remain unclear. Methods: A systematic literature search was conducted in PubMed, Embase, and Cochrane Library databases from January 2013 to October 2024. Randomized controlled trials (RCTs) comparing immunosuppressants (azathioprine) and biologics (TNF-alpha inhibitors - infliximab, adalimumab, etanercept) in adult BS patients were included. The primary outcomes were clinical response rates (defined as improvement in disease activity scores) and adverse events. A random-effects model was used to calculate pooled odds ratios (ORs) with 95% confidence intervals (CIs). Results: Six RCTs (n=785 patients) met the inclusion criteria. Biologics demonstrated significantly higher clinical response rates compared to immunosuppressants (OR 4.57, 95% CI 3.26-6.40, p<0.00001). Infliximab, adalimumab, and etanercept showed superiority over azathioprine (OR 4.40, 95% CI 2.33-8.30, p<0.00001; OR 5.51, 95% CI 2.86-10.61, p<0.00001; OR 4.19, 95% CI 2.54-6.92, p<0.00001, respectively). Adverse events were comparable between groups, with no significant difference in serious infections or malignancies. Conclusion: Biologics, particularly TNF-alpha inhibitors, are more efficacious than conventional immunosuppressants in inducing clinical response in BS, with similar safety profiles. These findings support the use of biologics as a first-line treatment option for moderate-to-severe BS.